#TITLE_ALTERNATIVE# - SAIFUL ANAM (NIM: 15011034),
Construction Basement is generally used as a parking area or a residential for several highrise buildings. As a ground building, construction should be considered appropriately. Basement construction is done by the method of top-down or bottom up. Both of type of method is based on the consideration of the construction area and the characteristics of the land where the construction. Both methods are focused on the influence of soil disturbance to the surrounding environment, the comfort of the construction process and the costs to be incurred in the project. Basement construction including retaining wall design for supporting disturbance affect by excavation. On this project, we will analyze the excavation of 50 x 70 m area and the excavation inside of 35 x 10 m by total depth 11 m, 6.5 m for 50 x 70 m excavation and 3.5 for 35 x 10 m excavation. The area of excavation is dominantly consist of clay, there are silty clay and clay. Two retaining system are available for this project, secant bored pile for 6.5 m excavation and concrete soldier pile for 3.5 excavation. On this retaining wall, strut are used to support the allÃ‚Â’strength. Structure used for secant pile is 880 diameter with 1200 spacing on it and installed by depth 21 m to the ground. For soldier pile, square soldier pile with 400 mm length are used with space about 600 m and installed by depth 13 m. Both of retaining wall system are installed by strut with profil 350 x 350 mm with 6 m space and length 12m for soldier pile and 14 m for secant pile wall. The strut modelled as fix end anchor with mohr coulomb and hardening soil for soil modeling. The whole construction are planned for 4 stage construction of excavation and two stage more for loading and installation of strut, for each type of excavation. The method of construction is braced excavation The analysis of excavation including safety factor analysis, deformation of retaining wal, deformation of soil excavation, force analysis on strut and retaining wall, dewatering analysis, and basal heave. PLAXIS 2D is used for modelling this case with undrained soil behavior (Type A) using effective parameter. This analysis give a conclusion that the excavation is passed the requirement of minimum Safety factor >1.5 and maximum deformation <45mm